Odpowiedzi

Najlepsza Odpowiedź!
2010-04-10T12:35:08+02:00
X - jedna liczba
y - druga liczba

½(x-y)=3
⅓(x+y)=10

½x-½y=3 |*2
⅓x+⅓y=10 |*3

x-y=6
x+y=30

x=6+y
6+y+y=30

x=6+y
6+2y=30

x=6+y
2y=30-6

x=6+y
2y=24 |÷2

x=6+y
y=12

x=6+12
y=12

x=18
y=12

spr
½(18-12)=3
½*6=3
3=3

⅓(x+y)=10
⅓(18+12)=10
⅓*30=10
10=10
2010-04-10T12:35:27+02:00
X- pierwsza liczba
y- druga liczba

x-y/2=3 (x+y)-1/3=10
x-y=6 te rownanie co mam wyżej mnożymy przez 3
x=6+y x+y=30
podstawiamy 6+y+y=30
2y=24
y=12
x=6+12 x=18